2018
DOI: 10.18006/2018.6(2).352.357
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF TEMPERATURE ON STERILITY IN CMS LINES OF PIGEONPEA [Cajanus cajan(L.) Millsp.]

Abstract: Present study includes five CMS lines of Pigeonpea with A4 cytoplasm at two locations viz. ICRISAT Patancheru (Telangana) and BAU Sabour (Bihar). Observations on each plant for pollen sterility were recorded at the onset of flowering in September. The second round of sterility evaluation was done in December. The final observations were recorded in February. Result of study revealed that higher temperature of ICRISAT Patancheru (Telangana) have positive effect on the sterility level and higher sterility was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The whole life cycle of H. armigera went up to 42 to 44 (43.16±0.74) days. The similar findings of total life cycle were reported by Kumar and Durairaj (2006); Chaitanya (2012) who reported that H. armigera life cycle of completed in 44.00 days and 42.8 days, respectively.…”
Section: Bio-ecology Of Important Borer Pest Of Pigeon Peasupporting
confidence: 88%
“…The whole life cycle of H. armigera went up to 42 to 44 (43.16±0.74) days. The similar findings of total life cycle were reported by Kumar and Durairaj (2006); Chaitanya (2012) who reported that H. armigera life cycle of completed in 44.00 days and 42.8 days, respectively.…”
Section: Bio-ecology Of Important Borer Pest Of Pigeon Peasupporting
confidence: 88%